Producción de cilantro (Coriandrum sativum) mediante la aplicación de tres diferentes dosis de abonos orgánicos. - García Villagómez, Víctor Félix (2023)
The research was carried out due to the need of diversifying the production through agroecological improvements in El Progreso precinct which is located in Pujili canton, Cotopaxi province. The following objectives were set: To evaluate the production of coriander (Coriandrum sativum) through the application of three different doses of organic fertilizers in Pujilí Canton. To dentify the appropriate dose of organic fertilizers on coriander cultivation (Coriandrum sativum). To determine the yield of coriander cultivation (Coriandrum sativum) by treatments. To analyze the production costs of the treatments in the cultivation. The evaluated variables were: number of leaves, stem diameter (cm), number of branches, plant height (cm), plant weight (g), and net weight of the plot (kg). The best results in the studied variables were plant height with a value of 23.67 (cm), number of branches with a value of 13.67 (units), number of leaves with a value of 53.22 (units), stem diameter with a value of 1.10 (cm), net weight of the plant with a value of 13.67 (g), and net weight of the plot with a value of 0.60 (kg); in the yield, 2000.00 kg/ha was obtained, so resulting the T7 Compost + 2.8 kg/m2 the best treatment with a positive benefit/cost of $0.35.